Toughening of polybutene-1 with form I′ induced by rapid pressurization. Issue 2 (1st December 2021) - Liu, Yanping; Wang, Yingchao; Zhang, Hongyu; Wu, Yuewen; Zhao, Shuo; Li, Qian; Shao, Chunguang; Wang, Zhen
Abstract : Combined with in situ wide angle X-ray diffraction, the mechanical properties of polybutene-1 with rapid pressurization are investigated. The toughness of polybutene-1 can be improved significantly by forms I/I′ produced by rapid pressurization. Abstract : Rapid pressurization (RP) induced crystallization of polybutene-1 (PB-1) is performed at different temperatures of 90 °C, 125 °C and 180 °C under various pressures. The mechanical properties of RP PB-1 are investigated with a tensile device and in situ wide-angle X-ray diffraction (WAXD) is used to record the structural evolution during deformation. Using differential scanning calorimetry (DSC) and WAXD, it is found that RP in the melt state produces forms I/I′, while stable form I with a high melting point is generated by RP at 90 °C. All three RP PB-1 samples at 180 °C have lower melting temperature of form I crystals, and their fracture strain is nearly three times that of normal form I. P1T90 shows a small fracture strain equivalent to that of normal form I, because RP at 90 °C only accelerates the phase transition from form II to I. Form I′ that directly crystallized from the melt state and the thinner lamellae of form I contribute to excellent toughness, which are conducive to the molecular orientation along the stretching direction. The optimization of toughness caused by rapid pressurization provides a new idea for the regulation of the mechanical properties of PB-1.